The Monumental Kurgans in Bronze Age in River Kura Basin - Najafov, Shamil N. (Global Journal of Cultural Studies, 2024)
The article contains with the archaeological excavations of the Deller Jayir kurgans at 322.700 km of the SCPX (South Caucasus Pipeline Expansion Project) pipeline corridor. These kurgans are located in the territory of Deller Jayir village of Shamkir district of Azerbaijan Republic. About 10 kurgans were recorded in the kurgan field located on a relatively high hill on the right bank of the river, about 100-150 m away from the Jayir River, only 2 of them fell into the pipeline corridor, excavated and explored. The surface of the Deller Jayir kurgans consists of stone formations with a clearly visible circular shape and a relatively concave center. They are located close to each other at a distance of 5-6 m. Preliminary analysis of the structures and burial rites in the Deller Jayir kurgans and the forms of the few pottery fragments found in these kurgans show that these kurgans date the transition stage from Middle Bronze Age to the Late Bronze Age, to be precisely, to the 15th-14th centuries BC.